2022
DOI: 10.3390/ma15113908
|View full text |Cite
|
Sign up to set email alerts
|

Improving Gamma Ray Shielding Behaviors of Polypropylene Using PbO Nanoparticles: An Experimental Study

Abstract: Recently, polymers have entered into many medical and industrial applications. This work aimed to intensively study polypropylene samples (PP) embedded with micro and nanoparticles of PbO for their application in radiation shielding. Samples were prepared by adding 10%, 30%, and 50% by weight of PbO microparticles (mPbO) and adding 10% and 50% PbO nanoparticles (nPbO), in addition to the control sample (pure polypropylene). The morphology of the prepared samples was tested; on the other hand, the shielding eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The mortars reinforced by nano-PbO showed higher LAC values than those containing micro-PbO at the same particle concentration and photon energy, indicating the particle size’s impact on enhancing the shielding capability. That is, the mortars filled with nano-PbO had better gamma-radiation-shielding efficiency than those loaded with micro-PbO, which agrees with the findings published in the literature [ 13 , 14 , 24 ]. As the size of PbO particles decreased from micro- to nanoscale, the particles became uniformly dispersed over the entire area within the mortar, which increased the interaction probability between the incident photons and the nanoparticles, thus increasing the chance of the photons undergoing more scattering and absorption processes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The mortars reinforced by nano-PbO showed higher LAC values than those containing micro-PbO at the same particle concentration and photon energy, indicating the particle size’s impact on enhancing the shielding capability. That is, the mortars filled with nano-PbO had better gamma-radiation-shielding efficiency than those loaded with micro-PbO, which agrees with the findings published in the literature [ 13 , 14 , 24 ]. As the size of PbO particles decreased from micro- to nanoscale, the particles became uniformly dispersed over the entire area within the mortar, which increased the interaction probability between the incident photons and the nanoparticles, thus increasing the chance of the photons undergoing more scattering and absorption processes.…”
Section: Resultssupporting
confidence: 91%
“…PbO is used to provide better shielding characteristics for high-energy gamma rays. Recently, El-Khatib et al studied the radiation-shielding properties of polypropylene (pp) samples embedded with PbO micro- and nanoparticles [ 13 ]. The results showed that pp embedded with nano PbO provided better attenuation than that of pp embedded with micro-PbO at all studied energies.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 d shows the results of changing the value of Z eff depending on the energy of shielded gamma rays, calculated according to the methodology proposed in [ 27 , 33 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be noted that in recent years, the research and development of various combinations of glass, polymer, and nanoparticle compositions for radiation protection has become a highly topical, and as a result, many different glass combinations have been successfully synthesized and evaluated [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MFP (cm) is defined as the average distance that a photon travels inside the sample without any interactions [ 36 ]: …”
Section: Methodsmentioning
confidence: 99%